Use of Trichoderma culture filtrates as a sustainable approach to mitigate early blight disease of tomato and their influence on plant biomarkers and antioxidants production - Imran, Muhammad; Abo-Elyousr, Kamal A. M.; Mousa, Magdi A. A.; Saad, Maged M. (Frontiers in Plant Science, 2023)
Alternaria solani is a challenging pathogen in tomato crop globally. Chemical control is a rapid approach but emerging fungicide resistance has become a serious threat. Present study investigates the use of Trichoderma culture filtrates (CFs) to control this disease. The CFs of T. harzianum, T. longibrachiatum and T. atroviride significantly inhibited the in vitro mycelial growth of A. solani (62.5%, 48.73% and 57.82% respectively followed by control 100%). In the GC-MS analysis of Trichoderma CFs volatile compounds viz., harzianic acid (61.86%) in T. harzianum, Linoleic acid (70.02%) in T. atroviride and Hydroxymethylfurfural (68.08%) in the CFs of T. longibrachiatum were abundantly present. Foliar application of CFs in greenhouse considerably reduced the disease severity (%) in all treatments viz., T. harzianum (18.03%), T. longibrachiatum (31.91%) and T. atroviride (23.33%) followed by infected control (86.91%) and positively affected the plant biomarkers. In the greenhouse, the plants treated with CFs demonstrated higher flavonoids after 6 days of inoculation whereas; phenolic compounds increased after 2 days. The CFs-treated plants demonstrated higher antioxidant enzymes i.e. Phenylalanine ammonia-lyase (PAL) and Peroxidase (PO) after 4 days whereas, Polyphenol oxidase (PPO) was higher after 6 days of inoculation followed by healthy and infected control. In open field conditions, disease severity in CFs-treated plants was reduced in both seasons as compared to naturally infected plants, CFs treated plants exhibited higher fruit yield than control. The present results conclude that CFs can be a potential biocontrol candidate and promising alternatives against the early blight pathogen for sustainable production.